Investigating the IT resources key factors in the Iraqi higher education institutions : a pilot study - A Fahad, A Meri, A Altaher, MA Dauwed, N Hashim, Sh Omar (Universiti Pendidikan Sultan Idris, 2017)
Investigating the IT resources key factors in the Iraqi higher education institutions : a pilot study by A Fahad, A Meri, A Altaher, MA Dauwed, N Hashim, Sh Omar,